Wage Problems in Indonesia in the Human Rights Perspective (Case of Inappropriate Wages for Pot Workers in Tangerang) - Zahra Zara Mahasin; Firqotun Naziah; Ridwan Arifin (The Indonesian Journal of International Clinical Legal Education, 2020)
This paper analyzes the fulfillment of rights for workers in the case in Tangerang (fulfillment of a decent salary). Whereas, one form of the implementation of the mandate of the 1945 Constitution in realizing decent livelihoods, especially for workers, is the minimum wage policy based on Law No. 13 of 2003 concerning Manpower which aims to provide protection for workers and their families, this is stated by clear in consideration of letter (d) of Law Number 13 of 2003 concerning Manpower, namely that the protection of labor is intended to guarantee the basic rights of workers and guarantee equal opportunity and treatment without discrimination on any basis to realize the welfare of workers and their families with still pay attention to the development progress of the business world. The disharmony in employment relations or labor turmoil is mostly caused by wage problems that are felt to be still very low. The low level of wages in Indonesia is caused by the abundant supply of labor, the level of labor skills is very low, and the government has an interest and seeks to create and expand employment opportunities.